2023
DOI: 10.1002/adfm.202212605
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Flammable Electrolyte with Lithium Nitrate as the Only Lithium Salt for Boosting Ultra‐Stable Cycling and Fire‐Safety Lithium Metal Batteries

Abstract: Lithium metal batteries (LMBs) attract considerable attention for their incomparable energy density. However, safety issues caused by uncontrollable lithium dendrites and highly flammable electrolyte limit large-scale LMBs applications. Herein, a low-cost, thermally stable, and low environmentallysensitive lithium nitrate (LiNO 3 ) is proposed as the only lithium salt to incorporate with nonflammable triethyl phosphate and fluoroethylene carbonate (FEC) co-solvent as the electrolyte anticipated to enhance the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…A plethora of prior research has demonstrated that the development of SEI films abundant in LiF and Li 3 N on the surface of lithium metal can significantly enhance the stability of the interface of lithium metal. [57][58][59][60] Therefore, the presence of higher amounts of LiF and Li 3 N in the SEI film may serve as a fundamental factor contributing to the superior performance of FMS-based electrolyte on lithiummetal anode compared to carbonates. In the aforementioned references, Li 3 N was generated through the addition of LiNO 3 as a film-forming additive.…”
Section: Key Components Of the Constructed Sei And Its Formation Mech...mentioning
confidence: 99%
“…A plethora of prior research has demonstrated that the development of SEI films abundant in LiF and Li 3 N on the surface of lithium metal can significantly enhance the stability of the interface of lithium metal. [57][58][59][60] Therefore, the presence of higher amounts of LiF and Li 3 N in the SEI film may serve as a fundamental factor contributing to the superior performance of FMS-based electrolyte on lithiummetal anode compared to carbonates. In the aforementioned references, Li 3 N was generated through the addition of LiNO 3 as a film-forming additive.…”
Section: Key Components Of the Constructed Sei And Its Formation Mech...mentioning
confidence: 99%
“…101,102 To take advantage of nitrogen-containing SEI formation on the lithium-metal anode, one should pair the use of LiNO 3 as an electrolyte additive with the use of high-donor number (high-DN) ethereal solvents such as 1,2-dimethoxyethane and tetraethylene glycol dimethyl ether. 103–105 However, as the DN (21.1 kcal mol −1 ) of the NO 3 − anion exceeds those of carbonate solvents (16.4 kcal mol −1 for EC, 17 kcal mol −1 for dimethyl carbonate, 16.0 kcal mol −1 for diethyl carbonate (DEC), and 9.1 kcal mol −1 for FEC), LiNO 3 is insufficiently dissociated in conventional carbonate-based electrolytes. 61,105 This limited dissociation can be enhanced through the use of solubilizers such as tris(pentafluorophenyl)borane, indium trifluoromethanesulfonate, and lithium tetrafluoroborate, additives with different cations, and organic nitrates such as isosorbide dinitrate.…”
Section: Regulation Of Sei Chemistry On Silicon and Lithium-metal Anodesmentioning
confidence: 99%
“…101,102 To take advantage of nitrogencontaining SEI formation on the lithium-metal anode, one should pair the use of LiNO 3 as an electrolyte additive with the use of high-donor number (high-DN) ethereal solvents such as 1,2-dimethoxyethane and tetraethylene glycol dimethyl ether. [103][104][105] However, as the DN (21.1 kcal mol −1 ) of the NO 3…”
Section: Regulation Of Sei Chemistry On Silicon and Lithium-metal Anodesmentioning
confidence: 99%
“…76 Jiang et al 77 employed FEC as the sacrificial additive to inhibit the decomposition of TEP, which effectively extended the cycle life of the LFP‖Li cell to 900 cycles at 1C employing 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in TEP with 2% FEC as the electrolyte. Liao et al 78 developed 1.5 M LiNO 3 TEP/FEC (3 : 1) that could form a stable Li 3 N–LiF-rich SEI on the Li anode owing to the higher binding energy of FEC with Li + than TEP (−2.01 eV vs. −2.66 eV) and the lower LUMO of NO 3 − compared to TEP. The LIBs exhibited a superior capacity retention of 96.39% and 83.74% after 1000 cycles at 1C for LFP‖Li and NCM811‖Li, respectively.…”
Section: Principles and The Design Strategies Of Nonflammable Electro...mentioning
confidence: 99%
“…161 In addition, utilizing LiNO 3 as a lithium salt leads to an ultra-stable organic–inorganic hybrid SEI film enriched with high ionic conductivity Li 3 N and LiF components, which can considerably enhance the anode stability for LIBs. 78…”
Section: Principles and The Design Strategies Of Nonflammable Electro...mentioning
confidence: 99%